Pressure Performance Analysis of Inclined Well under Multiple-Well Interference in Offshore Heavy Oil Reservoir. (13th July 2022) - Ma, Kuiqian; Wang, Gongchang; Gao, Yue; Wang, Meinan; Liu, Jianguo
Abstract : Offshore heavy oil reservoirs are developed mainly by inclined wells, and the well distance has been constantly reduced after several well network adjustments. The well test data are often interfered by adjacent wells, resulting in unsatisfactory well test interpretation results, so it is necessary to conduct studies on the multiwell interference well test problem for inclined wells. In this paper, the threshold pressure gradient of heavy oil and the stress sensitive to permeability are considered comprehensively, and a well test model of inclined wells in dual-media reservoirs under multiwell interference is established. The analytical solution in Laplace space is obtained by using Green function and superposition principle. The results show that the typical pressure dynamic curve can be divided into 12 flow regions, and the pressure derivative curve of the central inclined well is upturned and forms multiple "platforms" under the interference of adjacent wells; the adjacent well interference will aggravate the upward of pressure derivative curve; a critical well inclination angle of the inclined well is 40°. When the well inclination angle is greater than 40°, vertical radial flow similar to horizontal wells will appear. The new model is well matched and interpreted in the application of BZ oil field in Bohai Bay, which provides theoretical guidance for multiwell interference test wells in the similar reservoir.